Two opposing literary critiques of socialism: George Orwell versus Eugen Richter and Henry Hazlitt. (2016) - Makovi, Michael
Orwell's famous fictions, Animal Farm and Nineteen Eighty-Four criticised totalitarian forms of socialism from a public choice perspective, assuming that socialism would work as an economic system as long as the proper political institutions were in place to curb the potential for the abuse of power. This is contrasted with two novels by others who took the opposite approach: Richter's Pictures of the Socialistic Future and Hazlitt's Time Will Run Back. These two assumed that the political implementation of socialism would be perfect but that socialism would necessarily turn totalitarian because of the problem of economic calculation. These novels assumed away the public choice problem of institutions and the abuse of power and focused on the political implications of socialism as a purely economic system. Contrasting these two sets of novels shows how the Austrian and public choice schools criticise socialism in two entirely different ways.